A Study on Incidence Angle of Radiation in Anterior-Posterior Test of Sella Turcica - Jun Chae, Myung; Hwan Lim, Chung; hunJeung, Sung (International Journal of Engineering and Technology, 2018)
Background/Objectives: The general radiographic Test of Sella Turcica is conducted in the same manner as the Anterior-Posterior Test. The purpose of this study is to classify Sella Turcica by gender and age group in general radiological Test to provide basic data by presenting appropriate angle of incidence.Â Methods/Statistical analysis: This study was carried out with total 300 male and female patients from 20S to 70S who underwent Sella Turcica general radiography. The maximum length and the maximum width of the skull were measured in order to analyze the factors affecting OML and IOML angles and incidence angle.The t - test was conducted to compare and analyze the mean difference of IOML and OML angle, head length and breadth according to gender and age of the subjects. ANOVA analysis was conducted for comparative analysis of age and Duncan was used for Posterior test. Correlation analysis was conducted to analyze the variables affecting the incidence angle. The results of each analysis was considered to be statistically significant if the p-values were below p <.05.Â Findings: As a result of this study, the incidence angle was found to be 1.4 degrees higher than the reference point of 7 degrees in 300 subjects (p <.001) and was statistically significant. For the average incidence angle by age group, 60S showed the highest degree of 8.8 degrees and this is statistically significant (P<.001). Regarding the incidence angle by gender, the female showed 8.4 degrees while the male showed 8.3 degrees, means the female showed 0.1 degree higher than the male and this is considered to be statistically significant (P<.001). In both skull breadth and skull length, the male was significantly larger than female being statistically significant (p <.001). Skull breadth and skull length were significantly correlated (p <.01), but there was no significant difference between OML and IOML.Â Improvements/Applications: When conducting the General Radiation Test of Sella Turcica at a medical institution, age and gender should be considered.Â Â